Iranian Audacity & Israeli Opacity: Challenges to the Middle East Nuclear Weapons Free Zone - Bovey, Charles Daniel (My University, 2013)
A Nuclear Weapons Free Zone is a concept pre-dating the Treaty on the Non-Proliferation of Nuclear Weapons (NPT), 1968. Five such zones exist today covering more than 50% of the earth's surface. However, one region of the world, the Middle East, has no such agreement. This is in spite of the fact that none of the legitimate Nuclear Weapons States exist within this region and all but two nations are full adherents to the NPT - Israel, which never signed the NPT, and Iran, which has been sanctioned for violations of the safeguards agreement. This work attempts to explain the significance of the dichotomy between these two countries that directly challenge the establishment of such a zone, or restated, the Israel / Iran dynamic as a threat to establishment of a Middle East Nuclear Weapons Free Zone.
Thesis (Master's)--University of Washington, 2013
Keywords: Iran; NPT; Nuclear; Nuclear Weapons Free Zone; International relations; Peace studies; Middle Eastern studies; to be assigned